2023
DOI: 10.54393/pjhs.v4i10.1123
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of COVID-19 among Nurses at Mayo Hospital Lahore

Masooma Batool,
Ambar Afzal,
Sarah Naveed
et al.

Abstract: COVID-19 is an unparalleled global challenge, necessitating unprecedented interventions. It emerged as a new and highly contagious virus (SARS-CoV-2), causing high mortality rates and overwhelming healthcare systems. Nevertheless, prior experience with coronaviruses and recent epidemics has provided a foundation for effective infection control and the rapid development of vaccines and treatments. Objective: To assess knowledge attitude and practices regarding COVID-19 among nurses of Mayo Hospital Lahore. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…On the other hand, a Chinese study found that a higher income was associated with more understanding and the adoption of effective COVID- . The results from a study conducted in Jordan revealed that Jordanian nurses' comprehension of the COVID-19 disease falls within the "average" category, with the majority of their responses falling in the range of 56% to 86% [19]. The level of knowledge among the nurses was found to be associated with their years of experience in the healthcare eld, while their perceptions were in uenced by the manner in which they had received training for the care of .…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, a Chinese study found that a higher income was associated with more understanding and the adoption of effective COVID- . The results from a study conducted in Jordan revealed that Jordanian nurses' comprehension of the COVID-19 disease falls within the "average" category, with the majority of their responses falling in the range of 56% to 86% [19]. The level of knowledge among the nurses was found to be associated with their years of experience in the healthcare eld, while their perceptions were in uenced by the manner in which they had received training for the care of .…”
Section: Introductionmentioning
confidence: 97%